1982
DOI: 10.1093/jn/112.8.1546
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Sucrose, Fructose and Glucose on Carbohydrate-Induced Obesity in Rats

Abstract: Caloric intakes, body weights, plasma glucose levels and glucose tolerance were examined in male Sprague-Dawley rats given a single standard diet or the standard diet and one of four sources of sugar: 1) a 32% glucose solution, 2) a 32 % fructose solution, 3) a 32% sucrose solution or 4) granulated sucrose. After 50 days, blood was collected from fasted animals for analyses of serum glucose, triglycerides and insulin levels. Livers, kidneys, epididymal and retroperitoneal fat depots and intrascapular brown adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
89
0
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(106 citation statements)
references
References 29 publications
14
89
0
3
Order By: Relevance
“…Diets containing high amounts of carbohydrate, such as fructose, have been shown to cause weight gain and increase plasma triglyceride concentrations 33,34 . In a previous study it was shown that the rats fed on high-carbohydrate diets containing either a fructose/ glucose mixture or honey had a hypertriglyceridemia reaction and an increased lipid peroxidation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Diets containing high amounts of carbohydrate, such as fructose, have been shown to cause weight gain and increase plasma triglyceride concentrations 33,34 . In a previous study it was shown that the rats fed on high-carbohydrate diets containing either a fructose/ glucose mixture or honey had a hypertriglyceridemia reaction and an increased lipid peroxidation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…By the end of the study, chow/preferred-fed rats had gained 88% more body weight, owing to preferential accretion of visceral body fat, which increases the risk for cardiovascular disease and metabolic disease (Despres, 1993;Wajchenberg, 2000). The greater feed efficiency of chow/preferred-fed rats may result from the sucrose content of the preferred diet (Kanarek et al, 1987;Kanarek and Orthen-Gambill, 1982) as well as the acquired habit of consuming large energy loads following self-imposed periods of relative hypophagia (Batista et al, 1997). This self-determined 'meal-fed'-like pattern of sustained dietary restraint interrupted predictably by a single large meal/binge models eating patterns of some dieters and patients with eating disorders and, via greater prandial insulin responses (Calderon et al, 2004;Taylor et al, 1999), may promote lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, these studies showed that high glucose consumption causes an increase in body weight and abdominal fat associated with an increased protein oxidation induced by hyperglycemia, and that carbohydrate-induced obesity is not dependent on the sweet taste of carbohydrates. 6,21,22 Another important mechanism through which the intake of carbohydrates and particularly a glucose intake may be regulated is through a modulation of the intestinal serotonergic system. Indeed, previous studies have indicated that intestinal 5-HT3R might be involved in the detection and control of carbohydrate intake, such as glucose.…”
Section: Discussionmentioning
confidence: 99%